Effects of a phonics-integrated music rhythm intervention on reading fluency and accuracy with children - Dees, Laura; Cooper, Patrick K. (Frontiers in Human Neuroscience, 2025)
It is hypothesized that increasing literacy skills such as reading rate (fluency) and reading accuracy with children is possible through intentionally developed interventions focused on musical memory, timing, and production (e.g., clapping to a steady beat). Previous studies have found these effects to be significant with third-grade students, an age when school curriculum emphasizes literacy development. Using a quasi-experimental pretest-posttest design, we tested the effects of a musical intervention integrating English Language Arts (ELA) content from the Fundations program on rhythm and literacy skills with third-grade students aged eight to 10 (N = 164). Over 10 weeks, both control and experimental groups attended their regular music class, with the experimental group receiving a higher proportion of class time devoted to building rhythm skills. The most significant training effects were observed in rhythm growth scores: the experimental group showed greater pretest-posttest growth in rhythm skills (d = 0.57, p < 0.001). Correlations between rhythm and literacy skills were significant at both pretest-posttest time points (ρ = 0.20–0.35, p < 0.01). However, correlations between growth in rhythm and growth in literacy were not significant. Additionally, no significant differences in literacy growth were found between groups. While these results reinforce the cross-sectional links between rhythm and literacy skills, there was no evidence of transfer from musical growth to literacy growth. These results have practical significance by reporting a lack of training effects despite strong cross-sectional correlations and by discussing methodological considerations for evaluating potential causal effects of music training on academic outcomes.